Penentuan Parameter Rangkak pada Bentonit sebagai Bahan Penyangga (Buffer Material) dengan Uji Geser Langsung - Arintha I.D. Syafiarti; Huang Wei-Hsing; Chung Chih- Chung (Borneo Engineering : Jurnal Teknik Sipil, 2019)
A preliminary research to investigate the creep behavior of bentonite as buffer material in a high-level nuclear or radioactive waste disposal hole as bentonite needs to maintain the stability of the waste canister for a long time, to avoid the displacement caused by the weight of the canister itself and the thermal, hydrological, mechanical and chemical (THM-C) processes of the near filed. The increase of bentonite time-dependent strain or creep needs to be taken into account for the safety of the disposal hole. The creep parameters obtained from the angular strain rate equation, through stress-controlled direct shear test using compacted SPV200 bentonite samples. The test results show an increase in angular strain rate with increasing of the applied stress.